Analysis of hemorrhagic transformation and intracerebral hemorrhage under combination therapy with alteplase and antiplatelets or anticoagulants, using the Japanese Adverse Drug Event Report database. - Tsuyoshi Nakai; Takenao Koseki; Hiroka Nakao; Koki Kato; Kazuo Takahashi; Shigeki Yamada; Shoji Matsumoto (PLoS ONE)
Recombinant tissue-type plasminogen activators (rtPA) effectively dissolve blood clots and improve symptoms in patients with acute ischemic stroke and myocardial infraction. Although rtPA are used in patients taking antiplatelets or anticoagulants to improve clinical outcomes, combination therapy may increase the risk of hemorrhagic transformation (HT) and intracerebral hemorrhage (ICH). However, few studies have investigated the risk of HT and ICH associated with these combination therapies. This study aimed to investigate the adverse-event and drug-drug interaction signals for HT and ICH under combination therapy with alteplase and various antiplatelets or anticoagulants, using the Japanese Adverse Drug Event Report database. Adverse-event signals were evaluated using the reporting odds ratio and information components, and drug-drug interaction signals were studied using the Ω shrinkage measure, additive, multiplicative, and Chi-square statistics models. We also investigated predictors of HT and ICH, time-to-onset, and outcomes in patients receiving alteplase. HT and/or ICH signals were detected in patients receiving alteplase in combination with aspirin, P2Y12 inhibitors, cilostazol, ozagrel sodium, direct oral anticoagulants, warfarin potassium, heparin group, or argatroban. Hypertension and diabetes mellitus were significant risk factors for alteplase-induced HT. Most HT and ICH events occurred within 1 day after alteplase administration, and more than 60% of affected patients were not in recovery. In conclusion, continued monitoring is required in patients receiving alteplase in combination with any of the eight types of antiplatelets or the aforementioned anticoagulants. Additionally, the occurrence of HT or ICH within 1 day post-alteplase administration should be considered in patients with hypertension or diabetes mellitus. The findings from this study may help in understanding the risk of HT and ICH induced by rtPA in patients taking antiplatelet or anticoagulant medications, as well as in promoting the appropriate use of rtPA. Further prospective observational studies and randomized controlled trials are needed to assess these finding.